A rendezvous with the queen of ion channels: Three decades of ion channel research by David T Yue and his Calcium Signals Laboratory. Issue 1 (2nd January 2016) - Dick, Ivy E; Limpitikul, Worawan B; Niu, Jacqueline; Banerjee, Rahul; Issa, John B; Ben-Johny, Manu; Adams, Paul J; Kang, Po Wei; Lee, Shin Rong; Sang, Lingjie; Yang, Wanjun; Babich, Jennifer; et al.
Abstract : David T. Yue was a renowned biophysicist who dedicated his life to the study of Ca 2+ signaling in cells. In the wake of his passing, we are left not only with a feeling of great loss, but with a tremendous and impactful body of work contributed by a remarkable man. David's research spanned the spectrum from atomic structure to organ systems, with a quantitative rigor aimed at understanding the fundamental mechanisms underlying biological function. Along the way he developed new tools and approaches, enabling not only his own research but that of his contemporaries and those who will come after him. While we cannot hope to replicate the eloquence and style we are accustomed to in David's writing, we nonetheless undertake a review of David's chosen field of study with a focus on many of his contributions to the calcium channel field.